2011
DOI: 10.1093/europace/eur353
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of electroanatomical mapping during transseptal endocardial left ventricular lead implantation

Abstract: Electroanatomical mapping is a useful technical tool to guide endocardial LV lead implantation. It helps to identify the location of the transseptal puncture and the use of activation mapping might facilitate location of the optimal lead positions during CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In a recent sub‐analysis from the Alternate Site Cardiac Resynchronization (ALSYNC) study, Biffi et al found that prior non‐responders to CRT were able to improve on LV endocardial pacing via the trans‐septal route . Many experiences have been published on LV pacing via trans‐septal approach, but no randomized studies have compared its efficacy with that of the epicardial approach.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent sub‐analysis from the Alternate Site Cardiac Resynchronization (ALSYNC) study, Biffi et al found that prior non‐responders to CRT were able to improve on LV endocardial pacing via the trans‐septal route . Many experiences have been published on LV pacing via trans‐septal approach, but no randomized studies have compared its efficacy with that of the epicardial approach.…”
Section: Discussionmentioning
confidence: 99%
“…Venous anatomy dictates the limited number of sites at which LV pacing can be achieved with epicardial placement. A wider range of possible implant sites can be accessed via the endocardial approach allowing increased ability to select the hemodynamically optimal site 24 and risks of phrenic nerve stimulation are dramatically reduced. Although all techniques for TS endocardial LV pacing require a TS puncture, with the advent of atrial fibrillation ablation, this has become a maneuver that many electrophysiologists are comfortable with.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been reports of techniques to assist optimal LV site selection 24 . These approaches are, however, likely to be limited by the technical difficulty represented in maneuvering pacing leads across the interatrial septum and then on to optimal LV wall positions.…”
Section: Discussionmentioning
confidence: 99%
“…This latter technique is an alternative for superior transseptal attempts using standard equipment and it is also applicable for pacing sites that are more easily reachable by the femoral approach. During transseptal LV lead implantation, Kutyifa et al successfully applied electroanatomical mapping to identify the location of the transseptal puncture and to achieve an optimal LV lead position …”
Section: Alternative Techniquesmentioning
confidence: 99%